Limitantes de la política social para el desarrollo de la región Norte de México en contexto de la crisis económica mundial - Horbath, Jorge E.; Gracia, María Amalia (Sociedad y Economía, 2012)
The impact of the global crisis in Mexico, caused mainly by U.S. recession, has been of immense magnitude. In terms of regions, the Northern border has been the most hit. The basis of regional vulnerability and high dependency of this area are found in the absece of a solid structure of social policy linked to a regional industrialization strategy, which helps to build a strong productive balance with social basis. As a result of the fragmentation of Public Policy, social policy is currently being given the challenge of filling in the cracks left by economic policy.